2016
DOI: 10.1089/tmj.2015.0128
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Refinement of an e-Health Screening, Brief Intervention, and Referral to Treatment for Parents to Prevent Childhood Obesity in Primary Care

Abstract: RIPPLE may enhance parents' awareness of children's weight status and motivation to change their children's lifestyle behaviors but should be improved prior to implementation. Findings from this research directly informed revisions to our SBIRT, which will undergo preliminary testing in a randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…Nine studies were identified reporting user-testing by parents of digital health tools targeting improvements in children's nutrition. Five evaluated apps [18,[40][41][42][43], three evaluated websites [19,39,44] and one evaluated both an app and website [45] (Table 2; Additional file 3). Studies were conducted in the USA [41][42][43][44], Australia [18,19,45], Canada [40] and Switzerland [39].…”
Section: Objective Twowhat Do Parents Want From Digital Tools Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies were identified reporting user-testing by parents of digital health tools targeting improvements in children's nutrition. Five evaluated apps [18,[40][41][42][43], three evaluated websites [19,39,44] and one evaluated both an app and website [45] (Table 2; Additional file 3). Studies were conducted in the USA [41][42][43][44], Australia [18,19,45], Canada [40] and Switzerland [39].…”
Section: Objective Twowhat Do Parents Want From Digital Tools Supportmentioning
confidence: 99%
“…Five evaluated apps [18,[40][41][42][43], three evaluated websites [19,39,44] and one evaluated both an app and website [45] (Table 2; Additional file 3). Studies were conducted in the USA [41][42][43][44], Australia [18,19,45], Canada [40] and Switzerland [39]. Evaluations of preferences for content, features, technology, delivery mode, useability and barriers were conducted using focus groups [39][40][41][42]44] and questionnaires [18,19,39,41,43,45].…”
Section: Objective Twowhat Do Parents Want From Digital Tools Supportmentioning
confidence: 99%
“…Mobile devices increase the potential to promote healthy nutrition behaviors, and today nutrition and diet apps represent the fastest growing field of health promotion apps [4]. Mobile health (mHealth) apps for nutrition education can be suitable solutions to support parents’ involvement in childhood weight management interventions provided in primary care, as this is often the families’ first point of contact with the health care system [5,6]. The delivery of a primary care intervention by leveraging on digital and mobile support facilitates a higher compliance to it by the target users such as parents, who might have tight daily agendas, difficulties in tracking children’s weight-related behaviors over a day per week on paper diaries, and location difficulties [7].…”
Section: Introductionmentioning
confidence: 99%
“…The Resource Information Program for Parents on Lifestyle and Education (RIPPLE) represents an e‐health screening, brief intervention and referral to treatment (SBIRT) system for parents to help prevent childhood obesity in primary health care. It was viewed by the participants as practical, well‐designed and innovative; nonetheless, they recommended improvements to certain features, such as weight‐related terms, because they perceived it may evoke adverse responses from some parents …”
Section: Discussionmentioning
confidence: 99%
“…It was viewed by the participants as practical, well-designed and innovative; nonetheless, they recommended improvements to certain features, such as weight-related terms, because they perceived it may evoke adverse responses from some parents. 24 The MINSTOP (Mobile-based Intervention Intended to Stop Obesity in Preschoolers) is a web-and mobile phonebased intervention designed to help parents promote healthy eating and physical activity in children. Its effectiveness is still to be reported.…”
Section: Discussionmentioning
confidence: 99%